I. KANT, T. PARSONS AND POSTPOSITIVISM IN SOCIAL THEORY - Zenonas Norkus (Problemos, 1997)
Why does modern sociological theory designate itself with two names ("sociological theory" and "social theory")? These synonyms are interpreted in the article as a semantic symptom of the traditionally peculiar relations of sociology with other social sciences and philosophy. Sociology traditionally vacillates between the two definitions of its subject – the minimalist subject (the subject of sociology is a specific phenomena in society) and the maximalist subject (the subject of sociology is the society as a totality). If sociology defines itself as the science of society as a totality, it can take the shape of social theory and submerge itself into the dialectics of the antinomies of sociological reason. These dialectics are analogous to the dialectics of thinking about the world (nature) as a whole, which was brought to light by I. Kant in his "Critique of Pure Reasons." Social theory and philosophy of history are interpreted in the article as "metaphysics of modernity" succeeding traditional metaphysics. A path of the same shape as in the history of "pure metaphysics" before and after Kant can be traced in the histories of social theory and philosophy of history. Following Kant’s example of replacing metaphysics with the transcendental analytic of the naturlist intellect, W. Dilthey proposed the idea of transforming the philosophy of history into the critique of historical reason (critical philosophy of history). T. Parsons’ "The Structure of Social Action" can be interpreted as an attempt to design the critique of sociological reason. All three critiques keep company by assuming a substantive foundationalist concept of science. According to this concept, scientific knowledge is constituted by true, basic, necessary, and substantive (material) principles. This concept was assaulted by the positivist philosophy of science, upholding a formal procedural concept of the scientific method. Postpositivist philosophy of science denies the existence of theoretically neutral empirical knowledge and makes the procedures of the external control of the empirical theories problematic. It opens a logical space for a substantive discussion of the nonempirical assumptions of empirical theories (sociological theories included). The postpositivist philosophy of science as a forum for such a discussion fills in this space. By naming itselt "social theory," contemporary sociological theory reveals its permanent philosophical preoccupation with its foundations and its aspirations to serve as the integrating center for interdisciplinary cooperation of the social sciences. J. Alexander, A. Giddens, J. Habermas, and N. Luhmann are considered the most brilliant representatives of postpositivist social theory. J. Alexander’s "Theoretical Logic in Sociology" is singled out as deserving special attention because, in his attempt to develop postpositivist social theory, he chooses the classical work, (T. Parsons’) "The Structure of Social Action," as his main point of reference in the critique of sociological reason.